The prevalence and intensity of soil-transmitted roundworm infections and their correlation to the academic achievement of grade II students - Brion, Louella Flores (Animo Repository, 1993)
A parasitological survey was conducted on Grade II students enrolled during the school year 1992-1993, of General Tiburcio de Leon Elementary School. The study aimed to determine the prevalence and intensity of soil-transmitted roundworm infections among the students, and to correlate these infections with academic achievement. Stool specimen from 239 randomly-selected students were collected and preserved in 8 percent formalin solution. These formalinized stool samples were processed using the formalin-ether concentration technique (FECT), and the sediments were examined under the microscope. Prevalence of infection was determined by positive identification of parasite eggs. The intensity of infection was directly measured by counting the eggs per species detected during the examination. The over-all prevalence of soil-transmitted roundworm infection among these students was 5 percent. Trichuris trichiura and Ascaris lumbricoides were the predominant parasites detected, with prevalences of 46 percent and 36 percent, respectively. No hookworm infection was The grade point average (GPA) of the students for the school year 1992-1993 was used to measure their academic achievement. The students without infection had an almost similar GPA mean with students who had single infection. Students with mixed infections have the lowest GPA mean. The one-way analysis of variance (ANOVA) revealed no significant difference in the GPA means of the three groups of students. The Pearson r statistical test was used to correlate the grades of the students with and without infection. The test showed a low but significant correlation between the two variables (r = -.204, p 05). The Pearson r was also used to correlate students' GPA with different forms of infection : no infection, single infection and mixed infection. The test revealed a low but significant correlation between these variables (r The occurrence of only two (2) cases of moderate infection intensities, while all the other infected cases had light infection intensities, was thought to be the reason for the low correlation that resulted. This study, however, reiterated the importance of health in the education of school children.